Rola informacji w rozwoju przedsiębiorczości zespołowej - Krzyżanowska, Krystyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
In the paper an attention has been directed at the role the information plays in the collective entrepreneurship development. It includes problems such as: general conditions of information efficiency, the importance of information in the process of motivating, sources and scope of information preferred by farmers acting in producer groups. The study indicates that the most significant information resources explored by farmers, belonging to producer organisations, was advice provided by professionals. Generally, amongst these were found researchers from universities and foreign specialists. The value of delivered information was rated highly by horticulture producers. According to them, the information was straightforward, contemporary, practicable and included innovations. Either workshops or field abroad studies organised by agricultural extension centres were recognised as very significant and were placed at the top of information product list. During field studies farmers made familiar with well prospering producer groups. As a direct result of this program, farmers gained the opportunity to implement some pattern practices at their farms level and at the level of local communities. Surveyed horticulture producers favoured information on technology and marketing, then they chose economic and legal knowledge as well as this about benefits and risks resulting from hopeful accession of Poland with the European Union.